Säuglingsernährung und atopische Dermatitis - eine prospektive Beobachtungsstudie - Nentwich, Ivo; Pazdírková, Alexandra; Lokaj, Jindřich; Szépfalusi, Zsolt; Hrstková, Hana (Klinische Pädiatrie, 2009)
BACKGROUND: Recommendations for primary prevention of allergic diseases in high-risk children include hypoallergenic infant formulas (HA) if breastfeeding is insufficient. The primary objective of our study was to investigate the atopic dermatitis (AD) preventive effect of breastfeeding and HA-nutrition in the first 2 years of life and to follow the increase in weight.
Keywords: Risk Factors; Follow-Up Studies; prospektivní studie; Protein Hydrolysates; kojení; novorozenec; Milk Hypersensitivity; Humans; lidé; Body Weight; náhražky mateřského mléka; následné studie; Female; Immunoglobulin E; Male; Dermatitis, Atopic; Prospective Studies; Infant, Newborn; kojenec; mužské pohlaví; Infant; Breast Feeding; ženské pohlaví; Milk Proteins; neutrofily; Genetic Predisposition to Disease; tělesná hmotnost; Neutrophils; Infant Formula; alergie na mléko; mléčné bílkoviny; proteinové hydrolyzáty; genetická predispozice k nemoci; atopická dermatitida; imunoglobulin E; rizikové faktory